Feasibility of detecting snake envenomation biomarkers from dried blood spots. Issue 1 (22nd February 2023) - Smith, Cara F.; Brandehoff, Nicklaus P.; Pepin, Lesley; McCabe, Maxwell C.; Castoe, Todd A.; Mackessy, Stephen P.; Nemkov, Travis; Hansen, Kirk C.; Saviola, Anthony J.
Abstract: Biofluid proteomics is a sensitive and high throughput technique that provides vast amounts of molecular data for biomarker discovery. More recently, dried blood spots (DBS) have gained traction as a stable, noninvasive, and relatively cheap source of proteomic data for biomarker identification in disease and injury. Snake envenomation is responsible for significant morbidity and mortality worldwide; however, much remains unknown about the systemic molecular response to envenomation and acquiring biological samples for analysis is a major hurdle. In this study, we utilized DBS acquired from a case of lethal rattlesnake envenomation to determine the feasibility of discovering biomarkers associated with human envenomation. We identified proteins that were either unique or upregulated in envenomated blood compared to non‐envenomated blood and evaluated if physiological response pathways and protein markers that correspond to the observed syndromes triggered by envenomation could be detected. We demonstrate that DBS provide useful proteomic information on the systemic processes that resulted from envenomation in this case and find evidence for a massive and systemic inflammatory cascade, combined with coagulation dysregulation, complement system activation, hypoxia response activation, and apoptosis. We also detected potential markers indicative of lethal anaphylaxis, cardiac arrest, and brain death. Ultimately, DBS proteomics has the potential to provide stable and sensitive molecular data on envenomation syndromes and response pathways, which is particularly relevant in low‐resource areas which may lack the materials for biofluid processing and storage.